Central cementifying fibroma of maxilla - Mahnaz Sheikhi; Farzaneh Mosavat; Faranak Jalalian; Roghayeh Rashidipoor (Wolters Kluwer Medknow Publications, 2013)
Central cementifying fibroma is a bony tumor, which is believed to be derived from the cells of the periodontal ligament. Central cemento-ossifying fibroma behaves like, a benign bone neoplasm. This bone tumor consists of highly cellular, fibrous tissue that contains varying amounts of calcified tissue resembling bone, cementum, or both. Central cemento-ossifying fibromas of the mandible are common; however, they are rare in the maxilla region. This tumor is most frequent between 35 and 40 years of ages. In this report we have described a 37-year-old male with cemento-ossifying fibroma of the maxilla region with the mass that had been appeared 2-3 months prior to his first referral. Radiologic imaging such as intra-oral, panoramic, and Cone Beam CT had been performed. Histological analysis was done and finally diagnosis of central cementifying fibroma was made. The postoperative follow up at 12 months revealed no recurrence.